Peningkatan Literasi Kebencanaan Banjir Berbasis Data Geospasial pada Masyarakat Bantaran Sungai di Malang - Endang Surjati; Onik Farida Ni’matullah (Prosiding, 2026)
Communities residing along the riverbanks in Malang face a high risk of flooding, yet their understanding of geospatial data and disaster maps remains very limited. This community service activity aims to enhance flood disaster literacy through training in reading and interpreting maps and cartographic symbols relevant to riverside environments. The method employed was structured face-to-face training using a participatory approach involving fewer than 10 participants from riverside communities. Training materials covered three main components: (1) identification of flood-causing factors through analysis of topographic and land-use maps, (2) understanding flood impacts using risk and vulnerability maps, and (3) flood management strategies based on spatial data. Evaluation results showed a significant improvement in participants' knowledge across all three components, with a mean pretest score of 53.4 increasing to 80.7 on the posttest (N=20). All participants reported being able to read map legends, identify flood-prone zones, and plan evacuation routes based on maps. This activity demonstrates that geospatial literacy training is an effective approach for building community capacity in flood disaster preparedness.